Characteristics and Prognostic Significance of Preoperative Magnetic Resonance Imaging-Assessed Circumferential Margin in Rectal Cancer. (19th May 2015) - Ma, Xiaoji; Li, Xinxiang; Xu, Linghui; Shi, Debing; Tong, Tong; Huang, Dan; Ding, Ying; Cai, Sanjun; Peng, Junjie
Abstract : Purpose . To study the characteristics and prognostic significance of preoperative magnetic resonance imaging- (MRI-) assessed circumferential margin (CRM) in rectal cancer. Methods . Patients underwent preoperative high resolution pelvic MRI, followed by resection of primary tumor. The relationship between MRI-assessed CRM and pathological CRM (pCRM) was studied, and survival analysis was used to determine the prognostic significance of MRI-assessed CRM. Results . Of all the 203 patients, the total accuracy of MRI-assessed CRM for predicting involvement of pCRM was 84.2%, sensitivity was 50%, and specificity was 86.8%. Anterior tumors were more possible to assess involvement of CRM by MRI, while the false positive rate was significantly higher than lateral or posterior tumor (87.5% versus 50%, p = 0.0002 ). The 3-year local recurrence, disease-free survival, and overall survival rates were 35.6%, 58.1%, and 85.2% in patients with involved mrCRM, compared with 8.9%, 78.9%, and 92.3% in patients with clear mrCRM. In multivariate analysis, MRI-assessed CRM found an independent risk factor for local recurrence, with a hazard ratio of 3.49 (p = 0.003 ). Conclusions . High resolution MRI was accurate to assess CRM preoperatively, while anterior tumor should be assessed more cautiously. Involvement of mrCRM was significantly associated with local recurrence regardless of pCRM status.